2014
DOI: 10.1039/c4fo00154k
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hyperglycemia and TNFα-mediated inflammation by helichrysum and grapefruit extracts in diabetic db/db mice

Abstract: Type-2 diabetes is associated with a chronic low-grade systemic inflammation accompanied by an increased production of adipokines/cytokines by obese adipose tissue. The search for new antidiabetic drugs with different mechanisms of action, such as insulin sensitizers, insulin secretagogues and aglucosidase inhibitors, has directed the focus on the potential use of flavonoids in the management of type-2 diabetes. Thirty six diabetic male C57BL/6J db/db mice were fed a standard diet and randomly assigned into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…35,36 In our study, the levels of blood glucose and hepatic glycogen were significantly reversed after the rats were treated with alkylamides ( Fig. 40 Our results indicated that alkylamide treatment increased the GK expression and downregulated PEPCK and G6Pase expression levels in the liver of diabetic rats (Fig. On the basis of these findings, we hypothesized that alkylamides may modulate the critical enzymes of glycolysis and glycogen synthesis in the liver.…”
Section: Discussionsupporting
confidence: 53%
“…35,36 In our study, the levels of blood glucose and hepatic glycogen were significantly reversed after the rats were treated with alkylamides ( Fig. 40 Our results indicated that alkylamide treatment increased the GK expression and downregulated PEPCK and G6Pase expression levels in the liver of diabetic rats (Fig. On the basis of these findings, we hypothesized that alkylamides may modulate the critical enzymes of glycolysis and glycogen synthesis in the liver.…”
Section: Discussionsupporting
confidence: 53%
“…Flavonoid effects on inflammatory pathways NF-κB plays a key role in the intestinal inflammatory response (75) ; therefore, the compounds that could modulate this inflammatory pathway are an interesting field of investigation. Flavonoid-mediated modulation of the inflammatory response has been extensively studied in several in vivo and in vitro models (76)(77)(78)(79)(80) ; however, there are fewer studies regarding its effects on intestinal inflammation ( Table 1).…”
Section: Flavonoid Modulation Of Intestinal Inflammation Barrier Intmentioning
confidence: 99%
“…In the recent decades, the use of phenolic phytochemicals or natural extracts for the management of obesity and other related diseases has been a scientific focus [7,8]. In this sense, polyphenols such as flavanones (naringin), simple phenolic acids (coumaric acid and chlorogenic acid), curcuminoids (curcumin) [9], and other biocompounds, as for instance leucine, a branched-chain amino acid [10], have been suggested to exert potential health beneficial effects in the context of obesity.…”
mentioning
confidence: 99%